Characterization of Antibiotic Producing Rare Actinomycete Nonomuraea sp. JAJ18 Derived from an Indian Coastal Solar Saltern - Polpass Arul Jose; Kunjukrishnan Kamalakshi Sivakala; Pandiyan Rajeswari; Solomon Robinson David Jebakumar (The Scientific World Journal)
Rare actinomycete genera are accepted as a promising source of novel metabolites having pharmaceutical importance. One such genus of rare actinomycete is Nonomuraea. The present study was aimed at characterizing the antibiotic producing Nonomuraea strain JAJ18 which was previously isolated from coastal solar saltern. Strain JAJ18 was recognized as a member of genus Nonomuraea based on its almost complete 16S rRNA gene sequence and phenotypic characteristics. The strain JAJ18 was found to be closely related to Nonomuraea maheshkhaliensis 16-5-14T (98.90%), Nonomuraea candida HMC10T (98.58%), and Nonomuraea jabiensis A4036T (98.43%). From cell-free culture broth of strain JAJ18, an antibiotic was extracted and purified by silica column chromatography. The obtained antibiotic was found to be active against a range of Gram-positive and Gram-negative bacteria including drug-resistant Staphylococcus, with minimal inhibitory concentration (MIC) ranging from 0.5 to 16.0 µg mL−1. The structural characteristics of antibiotic were determined by FTIR and NMR spectroscopy. The antibiotic was identified to be an aliphatic rich compound with significant dissimilarity to known antibiotics reported from members of the genus, Nonomuraea. As the trends to discover novel metabolites from Nonomuraea are vibrant, further studies are needed to understand the structural and biotechnological significance of antibiotic compound produced by Nonomuraea sp. JAJ18.